Vector portraits, or, photography for the Anthropocene. (1st December 2015) - Coley, Rob
The Anthropocene, a concept to describe the planetary consequences of human culture, demands that we imagine the earth itself as an image-recording medium. It is a concept that confronts the entangled histories of industrialization and abstraction, revealing the thoroughly mediated circumstances from which perceptions of 'nature' emerge. This article considers an accelerated form of abstraction induced by technological capitalism, a form with thoroughly material consequences described by McKenzie Wark as 'vectoral'. If the age of the human is recorded on the earth, the vector is the tool of its stratigraphic inscription. Taking Tom McCarthy's novel Satin Island (2015) as an example, this article speculates on a photographic practice immanent to the vector. In Satin Island (2015), photographic images do not reinforce a human world but instead provoke a growing awareness of otherworldliness. These images confront the more radical and paradoxical consequences of the Anthropocene, an era that in fact names the end of the very category of human.